2021
DOI: 10.1177/2192568220984789
|View full text |Cite
|
Sign up to set email alerts
|

Costs Associated With Timely and Delayed Surgical Treatment of Spinal Metastases

Abstract: Study Design: Retrospective cohort study. Objectives: Symptoms caused by spinal metastases are often difficult to distinguish from symptoms caused by non-malignant spinal disease, complicating timely diagnosis, referral and treatment. The ensuing delays may promote the risk of neurological deficits or severe mechanical instability and consequent emergency surgery, leading to poorer prognosis. Presumably, treatment delay may subsequently lead to more health-care consumption and therefore increased average costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…if needed, which has improved outcomes and is more cost effective than delayed surgery. 17,18 Our sub-analysis demonstrated that only about 7% of the patients who presented to the ED were followed in a multidisciplinary spinal oncology clinic. Even among the small number of patients in this group, we demonstrated significantly longer systemic progression-free time.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…if needed, which has improved outcomes and is more cost effective than delayed surgery. 17,18 Our sub-analysis demonstrated that only about 7% of the patients who presented to the ED were followed in a multidisciplinary spinal oncology clinic. Even among the small number of patients in this group, we demonstrated significantly longer systemic progression-free time.…”
Section: Discussionmentioning
confidence: 94%
“…This points to the fact that early presentation to a multidisciplinary spinal oncology clinic can identify clinical changes at an earlier time point and provide treatments on the basis of diagnostic findings to prolong progression‐free survival. Earlier identification of progression can lead to improved care and more timely surgery, if needed, which has improved outcomes and is more cost effective than delayed surgery 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies across a number of spine surgeries suggest that delaying care negatively affects outcomes specifically leading to increased intraoperative bleeding, prolonged hospitalization, increased postoperative complications, and higher treatment costs. 14 , 30 , 31 Moreover, several studies have highlighted the prolonged pain and neurological debilitation patients experience as a result of treatment delay in addition to the reduced productivity and financial burden experienced on the part of the spine surgeon. 32 Therefore, it is our belief that clinicians and surgical centers can utilize our findings as a foundation with which to make informed decisions when enacting pre-, post-, and intra-operative protocol changes that undoubtedly affect patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we demonstrated that our DL model is reliable and may be used to automatically assess the Bilsky classification of metastatic epidural spinal cord compression on thoracic spine MRI. In clinical practice, the early diagnosis of spinal cord compression is important to prevent permanent neurological dysfunction ( 40 ). The DL model could be used to triage MRI scans for urgent reporting, augment non-sub-specialized radiologists when they report out of hours, and improve the communication and referral pathways between specialties including oncology, radiation oncology, and surgery.…”
Section: Discussionmentioning
confidence: 99%